Dorycnium pentaphyllum Extract Has Antiproliferative Effect on Human Cervix and Colon Cancer Cells. (2nd April 2020) - Demir, Selim; Yaman, Serap Ozer; Sener, Sila Ozlem; Ayazoglu Demir, Elif; Aliyazicioglu, Rezzan; Ozgen, Ufuk; Mentese, Ahmet; Deger, Orhan; Aliyazicioglu, Yuksel
Abstract: Although several studies have investigated the cytotoxic effects of different Fabaceae species, limited researches have been conducted on the cytotoxic effect of Dorycnium pentaphyllum . The aim of this study was to evaluate the phenolic characterization and the cytotoxic effect of D. pentaphyllum on human cervix (HeLa) and colon (WiDr) cancer cells and the possible mechanisms involved. Total phenolic content (TPC) and phenolic characterization of the extract were investigated using the Folin–Cioceltau method and RP-HPLC, respectively. The cytotoxic effect of the extract was evaluated using the MTT assay. The mechanism involved in the extract's cytotoxic effect was then evaluated in terms of apoptosis and the cell cycle using flow cytometry, while mitochondrial membrane potential (MMP) was investigated using the fluorometric method. The TPC value of the extract was 141.2 ± 0.8 mg gallic acid equivalent per g sample, and quercetin was detected as major phenolics. D. pentaphyllum extract exhibited a selective cytotoxic effect on HeLa and WiDr cells compared to normal fibroblast and colon cells, respectively. The extract induced cell cycle arrest at the S phase and apoptosis via reduced MMP in these cells. Further studies may be useful in developing a natural product based new generation pharmacological agent.